HUBUNGAN ANTARA STADIUM KEGANASAN NON-HEMATOLOGI DENGAN D-DIMER SEBAGAI INDIKATOR KEJADIAN TROMBOSIS - Wantera, I Putu; Bakta, I Made (journal of internal medicine, 2012)
Thrombotic complications are among the most common causes of death in patients with malignancy. D-dimer level is a persistent hemostatic activity sign and a predictor of a repeated thrombosis. This study was cross sectional study to knowcorrelation the level of D-dimer with the clinical stages of non-hematologic malignancy. Forty three consecutive patients with non-hematologic malignancy. All patients underwent D-dimer testing. The relationships between D-dimer and stages of non-hematologic malignancy were analised by spearman correlation. 43 patients with non-hematologic malignancy, 8 (18.6%) were in stage II with median D-dimer 445.0 mg/dL (226.25 Ð 959.25), 28 (65%) were in stage III with median D-dimer 1012.0 mg/dL (454.00 Ð 1632.75), 7 (16.3%) were in stage IV with median Ddimer 666.0 mg/dL (590.00 Ð 1721.00). Of 43 patients, 5 (11.6%) were with nasopharynx malignancy and median D-dimer level 628.0 mg/dL (380.00 Ð 3214.50); 19 (44.2%) were with cervix malignancy and median D-dimer 849.0 mg/dL (344.00 Ð 1458.00); 7 (16.3%) were with mammae malignancy and median D-dimer 617.0 mg/dL (380.75 Ð 1370.75); 4 (9.3%) were with lung malignancy and median D-dimer 1758.0 mg/dL (897.00 Ð 4361.00); 8 (18.6%) were with other malignancies and median D-dimer 675.3 mg/dL (412.0 Ð 1208.50). Median D-dimer levels had a tendency to increase as the stages of non hematologic malignancy were higher. However, D-dimer had no correlation to stages of non hematologic malignancy (correlation spearman 0.157; p=0.313 ). There is no correlation between D-dimer level and stages of non hematologic malignancies as an indicator of thrombosis. But there was a tendency of increasing level of D-dimer as the stages were increasing
Keywords: thrombosis, D-dimer, stages of malignancy, type of malignancy